Dissolution process at solid/liquid interface in nanometric metallic multilayers: Molecular dynamics simulations versus diffusion modeling. (15th October 2015) - Turlo, V.; Politano, O.; Baras, F.
Graphical abstract: Abstract: The dissolution process of Ni into liquid Al in a layered Ni–Al–Ni system is here studied by means of molecular dynamics simulations, using an embedded-atom method type potential. Molecular dynamics simulations allow us to describe the underlying microscopic mechanisms associated with the dissolution process and prove that the number of Ni dissolved is the key variable in following the progress of the reaction occurring in NiAl nanofoils. A diffusion-limited dissolution model has also been developed. This model is tractable enough to use simulation data to extract kinetic and thermodynamic parameters such as solubility, melting temperature and diffusion coefficients. The comparison with experimental data is satisfactory. The present work assesses the predominant role played by diffusion in the dissolution process at the nanoscale in layered systems.